Peacock's War - Peacock, Doug; McBride, Robert; McBride, Anne; Marcyes, Thomas; Earthrise Entertainment (Oley, PA : Bullfrog Films, 1987)
Vietnam veteran Douglas Peacock found refuge in an uninhabited wilderness by living and filming in grizzly bear country in Montana. He makes a powerful plea for wild places and for the grizzly bears who depend on that wilderness for their survival
Copy in DVD Format
Editor, Thomas Marcyes
VHS Format
Keywords: Grizzly bear; Documentary films